2022
DOI: 10.3934/mbe.2022418
|View full text |Cite
|
Sign up to set email alerts
|

Estimating relative generation times and reproduction numbers of Omicron BA.1 and BA.2 with respect to Delta variant in Denmark

Abstract: <abstract> <p>The Omicron variant spreads fastest as ever among the severe acute respiratory syndrome coronaviruses 2 (SARS-CoV-2) we had so far. The BA.1 and BA.2 sublineages of Omicron are circulating worldwide and it is urgent to evaluate the transmission advantages of these sublineages. Using a mathematical model describing trajectories of variant frequencies that assumes a constant ratio in mean generation times and a constant ratio in effective reproduction numbers among variants, trajecto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 16 publications
5
24
0
Order By: Relevance
“…This result is consistent with previous findings that support the higher infectiousness of Delta compared to Gamma (Du et al, 2022; Y. Liu & Rocklöv, 2022) and of Omicron (BA.1) compared to Delta (Nishiura et al, 2021; Suzuki et al, 2022; Ito et al, 2022; Ito et al, 2022a; Du et al, 2022). Using epidemiological and phylodynamics models, we estimate that the average Re of Omicron was ∼3 times higher than that of Delta.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This result is consistent with previous findings that support the higher infectiousness of Delta compared to Gamma (Du et al, 2022; Y. Liu & Rocklöv, 2022) and of Omicron (BA.1) compared to Delta (Nishiura et al, 2021; Suzuki et al, 2022; Ito et al, 2022; Ito et al, 2022a; Du et al, 2022). Using epidemiological and phylodynamics models, we estimate that the average Re of Omicron was ∼3 times higher than that of Delta.…”
Section: Discussionsupporting
confidence: 93%
“…Of note, the average relative Re of Omicron w.r.t. Delta in Amazonas (∼3) was roughly comparable to that estimated in other settings with different infection and vaccination histories like South Africa, Denmark, the UK, the United States of America, and India (∼2-5) (Nishiura et al, 2021; Suzuki et al, 2022; Ito et al, 2022a; Ito et al, 2022b; Du et al, 2022). The Omicron outbreak in Amazonas also had a similar duration from the onset of case growth to their peaks (∼30 days) than that observed in other populations with different immune landscapes (Washburne et al, 2022; van Dorp et al, 2022).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…27 Previous studies have reported different GTs for different variants of SARS-CoV-2. [28][29][30][31] Zhang et al 28 reported a mean GT of 2.9 days for B.1.617.2, while Hart et al 29 reported a mean intrinsic GT of 4.7 days and a mean household GT of 3.2 days for this variant. Ito et al 30 reported a reduction in mean GT for the Omicron variant BA.1 compared with the delta variant B.1.617.2 (GT for BA.1 = 0.44 to 0.46 times delta), and similar results were reported by Manica et al 31 .…”
Section: Methodsmentioning
confidence: 99%
“…The accumulation of genetic changes in S has been related to increased viral transmission compared with previous VOCs [3]. For instance, in Denmark and Italy, it has been estimated that BA.1 had an effective reproduction number (R t ) around two to three times greater than the Delta variant [4,5]. The large number of mutations in S resulted in an enhanced antigenic escape, reflected by the high number of infections among the vaccinated population and a sharp decline in the neutralization titers of reported monoclonal antibodies, as well as in the sera of vaccinated subjects [6,7].…”
Section: Introductionmentioning
confidence: 99%